Pengaruh Konsentrasi Starter Terhadap Kadar Alkohol, pH, dan Total Asam Tertitrasi (Tat) Whey Kefir - Anis Usfah Prastujati; Mustofa Hilmi; M Habbib Khirzin (Politeknik Negeri Jember, 2018)
Whey is a liquid produced from the separation of curd that its utilization is still very limited, so it can cause environmental pollution. The purpose of this study was to determine the effect of starter concentration on alcohol, pH, and total titrated acids in whey kefir. Pasteurized whey was added starter with concentration of 5, 7, and 9% (w/v) then incubated at 20Â°C for 24 hours. The research method used was Completely Randomized Design (CRD) with 3 treatments and 3 replications. The treatment used was cow milk added 5% starter as control (T0), whey added starter 5% (T1), whey added starter 7% (T2), and whey added starter 9% (T3). The data were analyzed using Analysis of Variance (ANOVA) and continued by Duncan Multiple Range Test (DMRT). The results showed that the higher starter concentration, the higher the alcohol content and tend to increase the total value of titrated acids (TTA).Â